Metaphor: The intertwinement of thought and language - Strauss, D. F. M. (Koers, 2011)
The analysis of this article aims at reflecting on the nature of metaphoricity within the context of thought and language – inspired by the contributions of Elaine Botha in this regard commencing about three decades ago. This paved the way for those who were working within the tradition of reformational philosophy to take a new look at the nature of metaphor. Since thinking and talking are concrete activities in principle functioning in all aspects of reality, they cannot as such provide criteria to decide on the order relationship between the logicalanalytical and lingual aspects of reality. It turns out that, without a proper view of the differences between concept and word, an account of the nature of metaphor remains inconsistent. Universal traits, logical objectification, and the conceptual unknowability of what is individual, surfaces in the article. The foundational role of spatial relationships appears to be linked to imaging and imagining, informing the proposal to differentiate between modally and entitary directed knowing. The linguistic turn in particular inspired a renewed interest in language and the central place of metaphorical language use. After considering the connections between analogy and metaphor a new approach to the distinction between modal analogies and metaphors is proposed – one that is geared towards the interconnections between the different dimensions of our experiential world. The last part is dedicated to Lakoff and Johnson (1999) who have developed a peculiar view of the “embodied mind”, “conceptual metaphor”, and “cross-domain mappings”, while the article concludes with an argument about the limits of substitution and take into account expanded conditions.